Interleukin-27 Disrupts the Crosstalk of Apoptotic Activities between 4T1 Breast Cancer Cells and M2 Macrophages - Mohd Yusof, Nurliyana; Mohamed Noor Fuadi, Natasha Nurafiqah; Hamid, Muhajir; Mohamed Alitheen, Noorjahan Banu; Mohd Hanafi, Nursyuhaida; Nik Abd Rahman, Nik Mohd Afizan (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Cytokine immunotherapy such as Interleukin-27 (IL-27) has been foreseen as a promising alternative anti-cancer treatment. Thus, this study aimed to investigate whether IL-27 gene therapy regulates crosstalk between breast cancer cells and macrophages in the sense of pro-apoptotic activities. Methods: This study has led to the development of recombinant pcDNA3.4-IL27. The recombinant pcDNA3.4-IL27 was transfected into 4T1 murine mammary carcinoma cells alone and co-culture of 4T1 with M2 macrophages. The successful expression of IL-27 in the cells were determine through the immunofluorescence staining and detection of CD206, M2 macrophages marker. Apoptotic effects of pcDNA3.4-IL27 were assessed through MTT assay, Annexin V flow cytometer analysis, and AO/PI dual staining. Results: Our findings shows that pcDNA3.4-IL27 has the ability to induce apoptosis in both of the cell group and performs better in the co-culture of 4T1 with M2 macrophages compared to 4T1 cells alone. PcDNA3.4-IL27 induced apoptosis through the altered cell morphology and reduction in the number of viable cells. Conclusion: These data demonstrate that pcDNA3.4-IL27 has the ability to induce apoptosis in both 4T1 cell alone and co-cultured 4T1 with M2 macrophages. Thus, could serve as a potential anti cancer candidate against breast cancer.